How to Reasonably Wait for the End of the World: Aquinas and Heidegger on the Letters to the Thessalonians - Oliva Mirela (De Gruyter, 2021)
For Christians, coping with a crisis requires a proper expectation of the end of the world. This article will discuss the experience of Thessalonians’ persecuted community, who receive solace and orientation from Saint Paul’s eschatological teaching. I will focus on Aquinas’ and Heidegger’s reading of Saint Paul’s letters to the Thessalonians. Their interpretation reveals two opposite ways of waiting for the end of the world, which pertain to two different modes of human rationality: (1) the calculative reasoning of those who claim to know when the end will happen, and (2) the lucidity and sobriety of the true believers, who accept that nobody can know the day of the second coming of Christ and thus we have to continually prepare and be ready for it. Which way is the most suited to handle a crisis like the current pandemic? The calculative reason is necessary for fields like medicine, which are crucial in defeating the pandemic. However, when dealing with a crisis that brings us unexpected and unknown circumstances, we also need the virtuous, sober, and awakened attitude promoted by Saint Paul in his letters and highlighted by Aquinas and Heidegger.